Dye Sensitized Solar Cel (DSSC) menggunakan Substrat Kaca GMR dan Bunga Rosella (Hibiscus Sabdariffa L.) sebagai Dye-Sensitizer - Hasanah, Uswatun (RC-INSTITUT, 2019)
Dye Sensitized Solar Cell (DSSC) is a photoelectrochemical solar cell where  convert sunlight into electrical energy. The purpose of this research is to determine the effect ofdye solution concentrationand time immersion to convert solar energy into electrical energy and the efficiency by DSSC. In this research, ZnO was coated on GMR and as  absorbent photon anthocyanin dye from rosella flower extract was used. Characterization of Giant Magnetoresistance (GMR) using Scanning Electron Microscopy (SEM). SEM  used to look the surface of the GMR. Characterization of light absorption using UV-Vis to known that anthocyanin can absorb the light at 540 nm. Based on research conducted DSSC managed to convert solar energy into electrical energy where the concentration variation obtained maximum efficiency of 0.249% at conentration 50% dye solution and maximum effeciency produced with variations in immersion time of 0.475% in 5 hours of immersion time.